The Psychological Method for Al -Aqqad - Qasem, Saleem (Journal of College of Education, 2022)
Our study was briefed in clarifying the concept of (criticizing the criticism) and highlighting in general the psychological method which is considered as one of the literary methods and which has strong bases in showing the creativity points of human self.This method also studies the behaviors, disorders and tempers of some poets such as Abi Nu'as, Ibn Al-Roumi, and Jameel Buthaina in how to solve the mystery of the key of each personality and its emotions, as the study has two orientations, the first one is psychological and the second is literary.
Keywords: psychological method; personality. Narcissism